Dependency and underdevelopment in the third world countries: A Nigeria experience - Ojo Oluwatoyin Emmanuel (Journal of Governance and Accountability Studies, 2023)
Purpose: This study aimed to examine dependency and underdevelopment in Nigeria. The themes of underdevelopment and dependency are used to characterize the social and economic circumstances of the third world. Research methodology: This article incorporates primary data through questionnaires, observations, and secondary data through consultation with several textbooks, magazines, journals, and other publications. Using simple random selection, thirty-seven out of 40 electronically presented surveys were completed. Results: The Nigerian economy is subject to the influence of the global political economy and the country does not have complete control over its economic system. Some elements, such as the actions of members of the economic elite and multinational firms, negatively impact the Nigerian economy. Limitations: Time constraints and availability of relevant literature, papers, and data are some of the main obstacles to the study project. Contribution: The findings will help policymakers and government officials develop effective economic strategies that address fundamental reasons for economic reliance.